Study of Respiratory Complaints Among Surface Coating Workers Due to Exposure to Particulates and Microbes - Indri Santiasih (Gema Lingkungan Kesehatan, 2024)
Surface coating generates particulates (PM2.5 and PM10), especially during sanding and painting. Particulates consist of several organic components, such as nitrates (NH3), ammonium (NH4+), and sulfates, which serve as substrates for microbes (bacteria and fungi) to proliferate. This study aims to analyze the effect of PM2.5 and PM10 concentrations and the concentrations of bacteria and fungi on respiratory complaints among workers in finishing areas. The independent variables studied are the concentrations of PM2.5 and PM10, as well as the concentrations of bacteria and fungi, while the dependent variable is the incidence of respiratory complaints. The statistical test used is binary logistic regression to examine the effects of the independent variables on the dependent variable. The results indicate that simultaneous exposure to PM10 and PM2.5 significantly affects respiratory complaints. The concentrations of bacteria and fungi also significantly affect respiratory complaints. Previous studies have shown that the size and diameter of particulates and their chemical composition are factors that negatively impact health. On the other hand, the concentrations of bacteria and fungi are positively correlated with particulate concentrations, as the organic substances in particulates allow bacteria and fungi to thrive. Microorganisms grow faster at 22–32°C temperatures and relative humidity between 40–90%. When the relative humidity reaches ≥80%, microbes are more likely to thrive and reproduce.